Burrows-Wheeler compression with variable length integer codes - Fenwick, Peter (Software, practice & experience, 2002)
The final coder in Burrows–Wheeler compression is usually either an adaptive Huffman coder (for speed) or a complex of arithmetic coders for better compression. This article describes the use of conventional pre‐defined variable length codes or universal codes and shows that they too can give excellent compression. The paper also describes a ‘sticky Move‐to‐Front’ modification which gives a useful improvement in compression for most files. Copyright © 2002 John Wiley & Sons, Ltd.